ARE CULTURAL AND GENDER DIVERSITY DRIVERS OF FIRM PERFORMANCE IN POST- CRISES EMERGENT ECONOMIES? - SUMEDREA, Silvia (Studia Universitatis Babeș-Bolyai Oeconomica, 2017)
https://doi.org/10.1515/subboec-2017-0005 The study aims to see if it could offer a positive response to the question whether the company's financial performance depends on diversity of ownership structure, board and management team. Studies of this type have been made in the developed financial markets, but hardly any were made in recent years in emerging markets. The results of this study on the Romanian financial market indicate that relationships between ownership structure, board and management team composition and firm performance are mixed. ROA, ROE, ROS and P/BV as measures of firm performance are influenced by the presence of foreign shareholders, top foreign managers, and the percentage of women managers and by company’s size. Boards including foreign members are more inclined to appoint foreign managers and women in firm’s managerial teams, but a small number of such persons are not positively associated with an increased financial performance of the firm. JEL Classification: C10, G34, M14, L25, M21